Nondestructive testing of delaminated interfaces between two materials using electromagnetic interrogation. (27th April 2018) - Cakoni, Fioralba; de Teresa, Irene; Monk, Peter
Abstract: We consider the problem of detecting whether two materials that should be in contact have separated or delaminated using electromagnetic radiation. The interface damage is modeled as a thin opening between two materials of different electromagnetic properties. To derive a reconstruction algorithm that focuses on testing for the delamination at the interface between the two materials, we use the approximate asymptotic model for the forward problem derived in de Teresa (2017 PhD Thesis University of Delaware). In this model, the differential equations in the small opening are replaced by approximate transmission conditions for the electromagnetic fields across the interface. We also assume that the undamaged or background state is known and it is desired to find where the delamination has opened. We adapt the linear sampling method to this configuration in order to locate the damaged part of the interface from a knowledge of the scattered field and the undamaged configuration, but without needing to know the electromagnetic properties of the opening. Numerical examples are presented to validate our algorithm.